JAROG DANCE FOR CHILDREN WITH SPECIAL Needs : Case Study in The Celebration of The International Dance Day in Surakarta - Wahyu, Eko (Harmonia: Journal of Arts Research and Education, 2013)
The International Dance Day is celebrated every year as a self-expression since dances belong to the world. Jarog dance was created to facilitate children with special needs in order to celebrate the International Dance Day in Surakarta in 2013. The research method applied was data collection consisting of observation, interview and documentation. The data analysis was the narrative one by using qualitative approach. The research result shows that Jarog is a new creation dance which combines Jaranan dance and Reog dance. The main functions of Jarog dance are character education, entertainment, and self-confidence improvement. Persistent learning, special commands by beating kendhang loudly and raising hands highly in every movement change and the rhythm of the instruments supporting the dance are needed. There were internal and external factors which support and obstruct the dance performance. The internal supporting factors were motivation, identification, sympathy and audienceâ€™s interest, while the external supporting factors were the influence of the world recognition, the motto â€Solo Berseriâ€, and the development of technology. The obstructing internal factors were the difficulties in practicing and adapting the movement, gendhing which was memorized easily, the beats of kendhang and other instruments which should have been louder. The external obstructing factors were the time-consuming rehearsal which interfered the childrenâ€™s study hours, less attention from their parents, and the poor cooperation with the supporting karawitan musicians.Â Hari tari dunia diperingati setiap tahun sebagai ekspresi diri karena tari dianggap sebagai milik dunia. Tari Jarog diciptakan untuk memenuhi anak berkebutuhan khusus dalam rangka merayakan hari tari dunia di Surakarta tahun 2013. Â Metode penelitian meliputi pengumpulan data yang terdiri atas observasi, wawancara dan dokumentasi. Analisis data bersifat naratip, dengan menggunakan pendekatan kualitatif. Hasil penelitian yang dicapai, Jarog merupakan tari kreasi baru yang menggabungkan antara tari Jaranan dengan tari Reog. Fungsi utama tari Jarog adalah sebagai pendidikan karakter, hiburan yang menyenangkan, dan meningkatkan kepercayaan diri. Diperlukan pembelajaran yang ulet, aba-aba khusus melalui pukulan kendhang yang keras dengan angkatan tangan yang tinggi pada waktu perpindahan gerak tari serta bunyi irama instrumen sebagai pendukung tari. Terdapat faktor Â yang mendukung dan menghambat dalam pentas tari, baik faktor internal maupun faktor eksternal. Faktor Â internal yang mendukung adalah motivasi, identifikasi, simpati dan animo penonton dari luar. Adapun faktor eksternal yang mendukung adalah pengaruh pengakuan dunia, slogan Solo berseri, dan perkembangan teknologi. Faktor penghambat dari dari dalam antara lain kesulitan dalam berlatih dan membiasakan gerak, gendhing mudah yang dihafal, bunyi kendhang dan instrumen tertentu harus lebih keras. Faktor penghambat dari luar antara lain pada saat berlatih Â menyita banyak waktu belajar, kurangnya perhatian orang tua, kerjasama dengan musik Â karawitan pendukungnya.